1979
DOI: 10.1007/bf00496847
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of infantile E. coli gastroenteritis with specific bovine anti-E. coli milk immunoglobulins

Abstract: A milk immunoglobulin concentrate (MIC) containing antibodies to enteropathogenic E. coli strains was prepared by hyperimmunisation of pregnant cows and using the milk obtained during the first 6 to 8 days of lactation. The sterile concentrate contained 70 to 80% protein and 35 to 40% immunoglobulin. The antibacterial activity was measured by bacterial passive agglutination, bacteriostatic activity in vitro, phagocytic clearance in vivo, and a protection test in mice. Though differences in titers were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(65 citation statements)
references
References 24 publications
2
62
0
1
Order By: Relevance
“…Guarino et al, 13 in Italy found the length of hospital stay was 76 hours in the group of acute diarrhea caused by rotavirus given antiviral human serum immunoglobulin compared to 131 hours in control group. In the Mieten et al's study, 14 bovine colostrum was given to 60 children with acute diarrhea by enteropathogenic E. coli (EPEC). This study results showed that 84.3% feces became E. coli negative after finishing the bovine colostrum treatment compared with 11.1% at the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Guarino et al, 13 in Italy found the length of hospital stay was 76 hours in the group of acute diarrhea caused by rotavirus given antiviral human serum immunoglobulin compared to 131 hours in control group. In the Mieten et al's study, 14 bovine colostrum was given to 60 children with acute diarrhea by enteropathogenic E. coli (EPEC). This study results showed that 84.3% feces became E. coli negative after finishing the bovine colostrum treatment compared with 11.1% at the control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, problems ofavailability, storage, and the possible transmission of infectious agents, such as cytomegalovirus, are factors that make widespread treatment or prophylaxis trials with human milk products difficult to accomplish. There have been several studies in man suggesting that passive immunity against infectious diarrheal agents may be achieved by the oral administration of immunoglobulin preparations derived from human or animal sera (12)(13)(14). To date, there have been no detailed studies of orally administered immunoglobulins in humans older than 13 wk ofage or in patients with chronic infectious diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…Enterotoxigenic E. coli strains are only an infrequent cause of gastroenteritis in the geographical area where the sera were collected. Only 9 out of 60 identified E. coli isolates from gastroenteritis patients hospitalized in Bochum/Germany belonged to enterotoxigenic E. coli serogroups (eight isolates were in fact of 0 78 serogroup [4], whereas 51 isolates belonged to enteropathogenic E. coli serogroups [4,9]. In addition only 22 % of the sera reactive with 0 78 antigen showed IgG antibody to the heat-labile enterotoxin according to the criteria of Levine and colleagues.…”
Section: Resultsmentioning
confidence: 98%
“…In the present report we investigated the possibility whether antibody to an individual 0 antigen (O 78) could be used as a serological marker for ETEC strain infection. 0 78 antigen was chosen because sera from volunteers orally challenged with ETEC strain 0 78 H11 were available to us [3] and because serogroup 0 78 was the most frequently isolated ETEC strain in the area where the scroprevalence study was conducted [4]. by heating in saline a suspension of washed E. coli grown on veal-infusion agar (Difco) for 1 h at 100°C [5].…”
Section: Introdictionmentioning
confidence: 99%